Archetype analysis of older adult immunization decision-making and implementation in 34 countries. Issue 26 (27th May 2020) - Privor-Dumm, Lois; Vasudevan, Prarthana; Kobayashi, Kana; Gupta, Jaya
Highlights: Immunization for older adults is an important strategy for healthy aging. We conducted a country archetype analysis of vaccine decisions and implementation. We found four distinct archetypes amongst the countries analyzed. Understanding country drivers & facilitators could help inform global strategies. Abstract: The global population of adults over 65 years of age is growing rapidly and is expected to double by 2050. Countries will face substantial health, economic and social burden deriving from vaccine-preventable diseases (VPDs) such as influenza, pneumonia and herpes zoster in older adults. It will be essential that countries utilize several public health strategies, including immunization. Understanding the different approaches countries have taken on adult immunization could help provide future learnings and technical support for adult vaccines within life-course immunization strategies. In this study, we describe the priorities and approaches that underlie adult immunization decision-making and implementation processes in 32 high-and-middle-income countries and two territories ("34 countries") who recommend adult vaccines in their national schedule. We conducted an archetype analysis based on a subset of two dozen indicators abstracted from a larger database. The analysis was based on a mixed-methods study, including results from 120 key informant interviews in six countries and a landscape review of secondary data from 34 countries. We found four distinct archetypes: disease prevention-focused; health security-focused; evolving adult focus; and, child-focused and cost-sensitive. The highest performing countries belonged to the disease prevention-focused and health security archetypes, although there was a range of performance within each archetype. Considering common barriers and facilitators of decision-making and implementation of adult vaccines within a primary archetype could help provide a framework for strategies to support countries with similar needs and approaches. It can also help in developing context-specific policies and guidance, including for countries prioritizing adult immunization programs in light of COVID-19. Further research may be beneficial to further refine archetypes and expand the understanding of what influences success within them. This can help advance policies and action that will improve vaccine access for older adults and build a stronger appreciation of the value of immunization amongst a variety of stakeholders.